Burgeoning hydrogel technology in burn wound care: A comprehensive meta-analysis. (15th August 2021) - George, Benu; Bhatia, Nitish; Suchithra, T.V.
Graphical abstract: Abstract: The largest and essential organ of our body, the skin, is a defensive layer. Damage to the skin affects the various functions and compromises the patient's working capacity and independence. Proper burn wound management considers patient's compliance and provides an environment to accelerate wound closure. A meta -analysis of large-scale data can reveal intrinsic observations. As a result, a meta -analysis was undertaken to elucidate the realm of polymers to design hydrogels for healing burn wounds. A total of 85 research articles were analysed to fully comprehend a hydrogel intervention in burn wound care. A bibliometric meta -analysis was carried out using a bibliometric R-package, Biblioshiny and VoS viewer of 85 research articles, exclusively focused on various aspects of hydrogel developments that have been briefly explained in this review. Furthermore, the data obtained from PubMed, from 2010 to 2020, focused on publications on medicinal plants used in burn wound management on animal models. This review constructs a holistic approach to analysing hydrogel technology for burn wound management. It briefly describes formulation development, drug release characteristics, computational modelling, phyto-based interventions and bioactive components and their molecular function through network analysis. Interestingly, the test extract formulations act on multiple targets that up-/down-regulate pathways and promote early wound closure by reducing inflammation-associated complications and wound infections. A systematic review by bibliometric analysis to explore hydrogel dressing for burn wounds streamline significant findings and formulation methodologies, assisting in developing superior wound dressing to address burn conditions.